Evolution of Raman G and G′ (2D) modes in folded graphene layers - Cong, Chunxiao (2014)
Bernal- and non-Bernal-stacked graphene layers have been systematically studied by Raman imaging and spectroscopy. Two dominant Raman modes, G and G ′ (or 2D ), of folded graphene layers exhibit three types of spectral features when interlayer lattice mismatches, defined by a rotational angle varies. Among these folded graphene layers, the most interesting one is the folded graphene layers that present an extremely strong G mode enhanced by a twist-induced Van Hove singularity. The evolution of Raman G and G ′ modes of such folded graphene layers are probed by changing the excitation photon energies. In this paper, doublet splitting of the G ′ mode in a folded double-layer (1 + 1) and of the G mode in a folded tetralayer (2 + 2) graphene are observed and discussed. The G ′ mode splitting in folded double-layer graphene is attributed to the coexistence of inner and outer scattering processes and the trigonal warping effect as well as further downward bending of the inner dispersion branch at a visible excitation energy. The two peaks of the G mode in folded tetralayer graphene are assigned to Raman-active mode (E 2g ) and lattice mismatch activated infrared-active mode (E 1u ), which is further verified by the temperature-dependent Raman measurements. Our study provides a summary and discussion of Raman spectra of Bernal- and non-Bernal-stacked graphene layers and further demonstrates the versatility of Raman spectroscopy for exploiting electronic band structures of graphene layers.